BIT@FK 2024 (June - July Edition) - Rahmah, Mokhtar; Fauziah, Zainuddin (Faculty of Computing, 2024)
In this edition, we proudly showcase the achievements of our faculty and students. Whether in research, competitions, industries collaboration or community projects, their successes highlight the quality of education and mentorship at our faculty.Our students have excelled in various areas, both nationally and internationally, demonstrating the skills and values we emphasise in our programmes. Our faculty members also continue to make important contributions through their research and leadership. The BIT@FK Bulletin is more than just a newsletter; it is a platform to promote the vibrant and supportive environment within our faculty. We aim to inspire and inform you through the articles in this edition, showing the talent and commitment that define our academic community.